Second‐line treatment of hepatocellular carcinoma after sorafenib: Characterizing treatments used over the past 10 years and real‐world eligibility for cabozantinib, regorafenib, and ramucirumab - Andrea S. Fung; Vincent C. Tam; Daniel E. Meyers; Hao‐Wen Sim; Jennifer J. Knox; Valeriya Zaborska; Janine Davies; Yoo‐Joung Ko; Eugene Batuyong; Haider Samawi; Winson Y. Cheung; Richard Lee‐Ying (Cancer Medicine, 2020)
Abstract Background The CELESTIAL, RESORCE, and REACH‐2 trials showed survival benefit of cabozantinib, regorafenib, and ramucirumab, respectively, in hepatocellular carcinoma (HCC) patients treated with sorafenib who had good performance status (ECOG 0‐1) and liver function (Child‐Pugh‐A). This study characterizes subsequent treatments received by HCC patients after sorafenib, and determines the proportion of patients eligible for novel therapies if strict eligibility criteria (SEC) were utilized compared to more liberal modified eligibility criteria (MEC, including ECOG 2, Child‐Pugh‐B7). Methods HCC patients who received sorafenib between 2008 and 2017 were included from the Canadian HCC CHORD Database. Patients were classified as eligible or ineligible based on available CELESTIAL, RESORCE, and REACH‐2 trial SEC or MEC. Median overall survival (mOS) was assessed using the Kaplan‐Meier method. Results A total of 730 patients were identified; and 172 (23.6%) received subsequent treatment. Patients who received subsequent treatment had longer mOS than those who did not (12.1 vs 3.3 months; P < .001). Using SEC, only 13.1% of patients would be eligible for cabozantinib, regorafenib, or ramucirumab. Expanding eligibility to include patients who meet MEC increased the proportion of eligible patients to 31.7%. Higher ineligibility for regorafenib and ramucirumab was driven by trial‐specific criteria, including sorafenib intolerance (28%) for RESORCE and AFP <400 (58.9%) for REACH‐2. Conclusions A small proportion of real‐world HCC patients would be eligible for cabozantinib, regorafenib, or ramucirumab if SEC in clinical trials were followed, while more than double would be eligible if MEC were applied. Patients who received subsequent treatment had improved mOS, regardless of whether they met SEC or MEC.